Orbit Determination of GPS and Koreasat 2 Satellite Using Angle-Only Data and Requirements for Optical Tracking System - Woo-Kyoung Lee; Hyung-Chul Lim; Pil-Ho Park; Jae-Hyuk Youn; Hong-Suh Yim; Hong-Kyu Moon (Journal of Astronomy and Space Sciences, 2004)
Gauss method for the initial orbit determination was tested using angle-only data obtained by orbit propagation using TLE and SGP4/SDP4 orbit propagation model. As the analysis of this simulation, a feasible time span between observation time of satellite resulting the minimum error to the true orbit was found. Initial orbit determination is performed using observational data of GPS 26 and Koreasat 2 from 0.6m telescope of KAO(Korea Astronomy Observatory) and precise orbit determination is also performed using simulated data. The result of precise orbit determination shows that the accuracy of resulting orbit is related to the accuracy of the observations and the number of data.